Doing business 2010 comparing regulation in 183 economies. - World Bank. (Washington, D.C. The International Bank for Reconstruction and Development/ The World Bank, 2009)
'Doing Business 2010' is the seventh in a series of annual reports comparing business regulations in 181 countries.
Cover title.
rua 13/06/14
Loans
Keywords: Commerce; Commercial policy; Business -- Costs -- Statistics